INSIGHTS FROM THE FRONT LINES: A COLLECTION OF STORIES OF HTA IMPACT FROM INAHTA MEMBER AGENCIES. (15th December 2017) - Schuller, Tara; Söderholm Werkö, Sophie
Abstract : This mini-theme contains six stories of health technology assessment (HTA) impact from member agencies of The International Network of Agencies for Health Technology Assessment (INAHTA), which were originally shared at the 2015 and 2016 INAHTA Congresses. The INAHTA impact story sharing is an innovative network activity where member agency representatives share experiences of HTA impact in a loosely structured story format. Through this process, members gain insights from other agencies on new ways of thinking about and approaching HTA impact assessment. A guide is provided to members to prepare their story, and the best story receives the David Hailey Award for Best Impact Story . This mini-theme contains stories of HTA impact from six member agencies in different parts of the world: the Health Assessment Division of the Ministry of Public Health (Uruguay), the Institute of Quality and Efficiency in Health Care (Germany), the Health Information and Quality Authority (Ireland), the Finnish Office for Health Technology Assessment (Finland), the Australian Safety and Efficacy Register of New Interventional Procedures-Surgical (Australia), and the Institut national d'excellence en santé et en services sociaux (Canada). Across the papers, common themes emerge about the importance of appropriate engagement of stakeholders and the broadening scope of HTA beyond reimbursement decision making.